25 Managing cardiovascular disease (CVD) risk factors in stroke and tia patients as part of an integrated community based preventive cardiology programme. (October 2018) - Gorecka, M; Gibson, I; Flaherty, G; Walsh, T; O'Donnell, M; Jones, J; Connolly, Susan; Crowley, J
Abstract : Introduction: Stroke is the leading cause of long-term morbidity in the developed world. Despite advances in medical care the absolute number of strokes is likely to increase in the coming decades as a result of ageing population. Furthermore, up to 25% of strokes occur in patients who previously suffered a stroke or a transient ischaemic attack (TIA). Effective stroke prevention strategies are therefore crucial. Whilst the evidence for stroke rehabilitation is well established, the evidence for structured secondary prevention programmes that address the risk factors for stroke (smoking, poor diet, sedentary behaviour, blood pressure, dyslipidaemia) is less well so. Here, we describe the results of a community-based preventive cardiology programme on a stroke/TIA population. Methods: Patients who had either a stroke or a TIA were invited to attend a community-based 16 week preventive cardiology programme delivered by a multi-disciplinary team (nurse, dietician, and physiotherapist) which included a weekly education and supervised exercise session. The foundation of the programme was healthy lifestyle change, but also the management of risk factors through the prescription of appropriate cardioprotective medication. An assessment was undertaken at baseline, end of programme (EOP) and 1 year follow up (FU) (table 1). Results: Between 2009 and 2016 a total of 227 patients were invited to the programme and 224 agreed to participate (response rate 98.7%). Referrals were received from the community and from hospitals. The majority were males (67.8%) with a mean age 65.1±10.6 years. 73.4% attended EOP assessment and 64.7% attended 1 year follow up. Table 1 summarises changes in lifestyle and medical risk factors between initial assessment and EOP and between IA and 1 year FU. By the end of the programme there was evidence of significant improvement in lifestyle, medical risk factors and psychosocial outcomes. The majority of these were maintained at one year. Conclusions: These data show that a nurse-led, community-based multidisciplinary preventive cardiology programme can provide effective secondary prevention for a stroke/TIA population. The improvements in both lifestyle and medical risk factors will also reduce their risk of a future cardiovascular event in the longer term.